Art, the sublime, and movement : spaced out - Du Preez, Amanda (New York, NY : Routledge, 2022)
"This book is a critical interdisciplinary approach to the study of contemporary visual culture and image studies, exploring ideas about space and place and ultimately contributing to the debates about being human in the digital age. The upward and downward pull seem in a constant contest for humanity's attention. Both forces are powerful in the effects and affects they invoke. When tracing this iconological history, Amanda du Preez's starts in the early nineteenth century, moving into the twentieth century and then spanning the whole century up to contemporary twentieth-first century screen culture and space travels. Du Preez parses the intersecting pathways between Heaven and Earth, up and down, flying and falling through the concept of being "spaced out." The idea of being "spaced out" is applied as a metaphor to trace the visual history of sublime encounters that displace Earth, gravity, locality, belonging, home, real life and embodiment. The book will be of interest to scholars working in art history, visual culture, media and cultural studies, phenomenology, digital culture, mobility studies, and urban studies"--
Keywords: Sublime, The; Art -- Philosophy; Aesthetics; ART / History / Modern (late 19th Century to 1945)